2018
DOI: 10.1002/ijc.31721
|View full text |Cite
|
Sign up to set email alerts
|

A Nationwide Cohort Study on the risk of non‐gynecological cancers in women with surgically verified endometriosis

Abstract: We assessed the association of surgically verified endometriosis and risk of non-gynecological cancers according to the type of endometriosis (i.e., ovarian, peritoneal and deep infiltrating endometriosis). All diagnoses of endometriosis combined with relevant procedural codes were identified from the Finnish Hospital Discharge Register 1987-2012. Non-gynecological cancers diagnosed after the endometriosis diagnosis were obtained from the Finnish Cancer Registry. The cohort of 49,933 women with surgically veri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 47 publications
(53 reference statements)
1
10
2
1
Order By: Relevance
“…These studies included women from different age groups, which also may contribute to the identified variations in the estimates. There were two studies utilizing data from hospital discharge databases and one study with self-reported endometriosis, which included women over 60 years (n = 425) and between 55 and 70 years of age (n = 747) and women older than 56 years (n = 471), respectively [11,28,29]. The main symptoms were infertility, peritoneal adhesions, genital pain, and ovarian cyst or growth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies included women from different age groups, which also may contribute to the identified variations in the estimates. There were two studies utilizing data from hospital discharge databases and one study with self-reported endometriosis, which included women over 60 years (n = 425) and between 55 and 70 years of age (n = 747) and women older than 56 years (n = 471), respectively [11,28,29]. The main symptoms were infertility, peritoneal adhesions, genital pain, and ovarian cyst or growth.…”
Section: Discussionmentioning
confidence: 99%
“…The main characteristics of the studies included in this review are shown in Table 1. The papers were published between 1989 and 2019 and originated from Norway [10], Denmark [11], the USA [12,16,19,20,25,26,33,35], Australia [13,14], Puerto Rico [15], Sweden [17], Japan [18], the UK [21,22], Israel [23], Germany [24], Iceland [27], Finland [28], Canada [29], Italy [30,32,34,36], and France [31]. The age of participating women varied in different studies from the minimal age of 10 years and older.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Среди других онкологических заболеваний наиболее часто связывают с эндометриозом неходжкинскую лимфому [6, 10, 11] и меланому кожи [6,10,11,29]. В небольших исследованиях также сообщалось, что женщины с эндометриозом подвергаются повышенному риску развития злокачественных опухолей органов эндокринной системы [11], головного мозга [11], рака щитовидной железы и почки [11,30], базальноклеточного рака [11,30].…”
Section: Discussionunclassified
“…Liisu Saavalainen et al found an increased risk of thyroid cancer in the entire cohort and in the sub-cohorts of ovarian and peritoneal endometriosis. That was especially seen for thyroid cancer with papillary histology [34].…”
Section: Non-gynecological Cancersmentioning
confidence: 96%